Research on the driving paths of bilateral renewable energy trade between neighboring countries and China from the perspective of behavioral attribution - Zijie Yang (Environmental Research Communications)
The bilateral trade in renewable energy between China and its neighbors represents a global cooperative endeavor influenced by various factors. However, few studies have conducted a comprehensive examination of the behavioral attribution-based reasons behind the bilateral cooperation in renewable energy between China and its neighbors. This study breaks down the aspects of cooperation willingness, cooperation capability and cooperation environment, along with their respective components, based on international behavioral attribution theory. To determine the configurational pathways of each constituent element’s role in the bilateral renewable energy trade cooperation between each case country and China, this paper employs a mixed-method approach of Necessary Condition Analysis (NCA) and fuzzy-set Qualitative Comparative Analysis (fs-QCA), selecting 20 ‘country-stage’ cases based on data availability. The study finds that for neighboring nations to engage in substantial renewable energy trade with China, extensive use of market-incentive policy instruments is essential. Additionally, favorable bilateral political ties, a lower level of nationalism and increased energy security within surrounding nations are critical factors in fostering extensive renewable energy trade with China. Meanwhile, the economic vulnerability and reliance of different nations on China have varying impacts on their final trade in renewable energy with China. The study identifies five configurational pathways that drive large-scale renewable energy trade cooperation between neighboring countries and China, as well as four configurational pathways that constrain such cooperation.